Analisis dan Perancangan Sistem Informasi Penjualan Berbasis Web dengan Metode RAD (Rapid Application Development) di Toko Largurda AM Store - Fauzi, M.; Verry, Verry; Haq, Abdul (Universitas Methodist Indonesia, 2024)
Largura AM Store is a fashion store with a large customer base that operates through offline sales, making it challenging to reach a broader market. This research aims to analyze, design, and develop a web-based sales information system for Largura AM Store using the Rapid Application Development (RAD) method with a Unified Modeling Language (UML) approach, which includes requirements planning, prototyping, testing, refining, development, and implementation. This technological advancement not only simplifies store management but also enhances the customer experience by facilitating product selection, payment, and tracking of shipment status. Using the RAD method, this research focuses on developing a website using Laravel as the framework for sales transactions. This study indicates that adopting a web-based sales information system can potentially improve store management effectiveness and the overall transaction process. The system development results were tested using black-box testing with questionnaires as the evaluation model. In conclusion, this system serves as an effective solution to optimize store operations and expand the reach to new customers and consumers.